2020
DOI: 10.1007/s10863-020-09844-6
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA-AK149641 associated with airway inflammation in an OVA-induced asthma mouse model

Abstract: Asthma is defined as a heterogeneous disease, usually characterized by chronic airway inflammation. Long noncoding RNAs (lncRNAs) play important roles in various biological processes. To know more about the relationships between lncRNAs and asthma, gene microarray analysis was performed to screen differentially expressed lncRNAs between the lung tissue of ovalbumin (OVA) mice and control mice. Further studies showed that downregulating differentially expressed lncRNA-AK149641 by adeno-associated virus 6 (AAV6)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 44 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…Therefore, IL-6 is a key factor in regulating the pathogenesis of AR induced by the imbalance of Th1 and Th2 differentiation [ 41 ]. The research shows that down-regulated lncRNA-AK149641 can decrease the expression level of TNF- α and IL-6 by the activity of the NF- κ B signaling pathway in OVA mice [ 42 ]. We have mentioned that respiratory syncytial virus (RSV) infection is a risk factor for allergic rhinitis.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, IL-6 is a key factor in regulating the pathogenesis of AR induced by the imbalance of Th1 and Th2 differentiation [ 41 ]. The research shows that down-regulated lncRNA-AK149641 can decrease the expression level of TNF- α and IL-6 by the activity of the NF- κ B signaling pathway in OVA mice [ 42 ]. We have mentioned that respiratory syncytial virus (RSV) infection is a risk factor for allergic rhinitis.…”
Section: Introductionmentioning
confidence: 99%
“…The asthma model, which is characterized by airway inflammation, can be induced by OVA stimulation for less than 30 days [ 9 ]. In this study, to establish asthma model characterized by airway remodeling, we prolonged OVA stimulation to 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA BCYRN1 could facilitate the proliferation and migration of ASMCs of asthmatic rat through up-regulation of transient receptor potential [ 8 ]. Down-regulating lncRNA-AK149641 in OVA-induced asthmatic mice could alleviate airway inflammation, mucus secretions, decrease expression of interleukin-6 and tumor necrosis factor alpha [ 9 ]. LncRNA Malat1 could inhibit the platelet-derived growth factor BB mediated ASMCs proliferation and migration through miR-150-eIF4E/Akt Signaling in the airway remodeling in asthma [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the literature has reported that lncRNA expression profiles in immune cells of AR patients and animal models are equally cell-specific [144,145]. Ma [118] lncRNA-TUG1 Downregulation miR-29c/B7-H3 Promote Th2 cell differentiation [20] lncRNA-AK085-865 Downregulation Unknown Ameliorate inflammation [119] lncRNA-BCYRN1 Downregulation miRNA-150 Inhibit the proliferation of ASMCs [113] lncRNA-LINCPINT Downregulation miRNA-265p/PTEN Retard the abnormal growth of ASMCs [120] circRNA-0005519 Upregulation miRNA-7a-5p Increase IL-6/IL-13levels [82] circRNA-HIPK3 Upregulation miR-326/STIM1; miR-375/MMP-16 Modulate the proliferation of AMSCs [85,121] circRNA-0002594 Upregulation Unknown Upregulate in CD4 + T cells [86] CircRNA-ZNF652 Upregulation miR-452-5p/JAK2 Promote the goblet cell metaplasia [122] circRNA-ERBB2 Downregulation miR-98-5p/IGF1R Increase infiltration [123] 6 Mediators of Inflammation et al [146] found that the expression profiles of lncRNAs were significantly cell-specific and involved multiple signaling pathways associated with AR disease development by comparing the expression profiles of lncRNAs in CD4 + T cells from AR mouse models and control mice by sequencing. In parallel, some lncRNAs have been proven to be potential biomarkers for assessing AR severity and progno-sis.…”
Section: Lncrna and Armentioning
confidence: 99%